Compliance under fragmented governance: the case of ASEAN economic community implementation in four Indonesian city governments. (2nd November 2018) - Lele, Gabriel
ABSTRACT: This article assesses the degree of compliance with international commitments by looking at the dynamics of policy implementation in four Indonesian city governments in implementing the conditions of ASEAN Economic Community reform. The article identifies an implementation gap between formal international commitments and their achievement in practice. The nature of Indonesian governance explains the gap and brings into focus central-local government relationships under highly formally decentralized systems. While forging international commitments is an exclusive responsibility of central government, the implementation of those commitments unavoidably brings in local governments. Local governments under a decentralized system may lack the knowledge or capacity to implement decisions. They may have political and economic interests that encourage non-compliance. Both sets of factors feature in this study.